Strategi Pengelolaan Dana Infaq dan Shadaqah Melalui Program Koin Peduli pada Musim Pandemi Covid-19 (Studi pada LAZISNU MWC Ngronggot Nganjuk) - Mahfudhotin; Rifda Lulus Madani (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2022)
This research was conducted with the aim of describing the concept of a solution to help alleviate poverty and economic hardship in the Covid-19 pandemic season through infaq media. LAZISNU as one of the ZIS charity institutions in Indonesia which has an infaq management program, namely the NU Peduli Coin Program. The purpose of this study was to find out how infaq management was carried out by LAZISNU MWC Ngronggot Kediri through the NU Peduli Coin Program. This study used descriptive qualitative methods to provide an overview of program management using interviews, documentation, and observation techniques. The results of this study reveal that the NU Peduli Coin Program strategy has a flow concept starting with fundraising management followed by fund management and ending with the management of distributing infaq funds to those in need. This program had a positive impact on both LAZISNU and mustahiq elements. It is also known that the LAZISNU MWC Ngronggot Kediri management as amil in managing this program is voluntary without being paid a penny as a form of dedication to Nahdlatul Ulama.